2017
DOI: 10.4103/jehp.jehp_107_15
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating combined effect of noise and heat on blood pressure changes among males in climatic chamber

Abstract: INTRODUCTION:Exposure to noise and heat causes individuals to experience some changes in the function of cardiovascular system in workplaces. This study aimed to find the combined effect of heat and noise on systolic and diastolic types of blood pressure in experimentally controlled conditions.METHODS:This quasi-experimental study was performed with 12 male students in a climatic chamber in 2014. Blood pressure including systolic and diastolic was measured in the following conditions: 15 min after rest in expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 21 publications
(27 reference statements)
1
4
0
Order By: Relevance
“…In regards to occupational noise levels above 85 dB(A), the association between noise exposure and hypertension is inconsistent. Some researchers have showed that occupational noise exposure is associated with a higher risk of hypertension or with a sustained elevation of blood pressure 1,2,22,23 , which is consistent with our findings (Table 2). Still, other studies have not suggested any significant link 11,24,25 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In regards to occupational noise levels above 85 dB(A), the association between noise exposure and hypertension is inconsistent. Some researchers have showed that occupational noise exposure is associated with a higher risk of hypertension or with a sustained elevation of blood pressure 1,2,22,23 , which is consistent with our findings (Table 2). Still, other studies have not suggested any significant link 11,24,25 .…”
Section: Discussionsupporting
confidence: 93%
“…Exposure to occupational noise in relation to occupational injuries has become a legitimate public health issue in recent years. In addition to incurring adverse effects on the auditory system, noise, as a stressor and one of the most harmful agents for workers, may also cause elevated blood pressure, anxiety, angiocardiopathy, and impaired hormone secretion 14 . Many studies suggest that along with hearing difficulty, noise exposure has been especially associated with cardiovascular diseases such as arteriosclerosis, hypertension, and coronary heart disease 58 .…”
Section: Introductionmentioning
confidence: 99%
“…Another experimental study performed in a climatic chamber observed that the mean change of systolic blood pressure was different significantly before and after exposure to heat and noise levels including 75, 85, and 95 dB ( p = 0.015, p = 0.001, p > 0.001, p = 0.027, respectively). Although systolic and diastolic blood pressures changed drastically, it was not significantly different in simultaneous exposure to heat and noise [ 12 ]. Despite the odds of carotid plaque being higher in the combination group than either single group in our study, no significant multiplicative or additive interactions between the heat stress and noise were observed.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of independent and combined physical hazardous agents on health is varied. Combined exposure to noise and heat has more of a detrimental effect on salivary cortisol and blood pressure as compared to independent exposure [ 11 ], while another study showed that subtle changes of blood pressure were traced when exposed to a combination of heat and noise [ 12 ]. Several underlying mechanisms have been shown to be likely involved in the development of these exposures to atherosclerosis: heat stress can increase the production of reactive oxygen species (ROS), induce apoptosis, and increase peripheral circulation and sweating, which could increase the plasma viscosity and serum cholesterol level, and promote the genesis and development of atherosclerosis [ 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…An exposure-response relationship between prevalence of hypertension and noise exposure as a persistent occupational and environmental problem was indicated in previous studies (Jarup et al, 2008;Rosenlund et al, 2001;Osadad, Yamamotoa, 2004). Exposure to high level of noise can cause increase in stress levels leading to adrenalin augmentation, increase in cortisol level, superficial vascular constriction, and as a result, raised blood pressure (Dehghan et al, 2017;Bigert et al, 2005;van Kempen et al, 2002).…”
Section: Introductionmentioning
confidence: 87%